Feasibility Study Of Mustahik As Zakat Recipient Through Productive Program (UMKM) At Lazismu Kudus - Wijayanti, Irma Aryani; Qomar, Moh. Nurul (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2023)
This study aims first, to determine the eligibility of mustahik as zakat recipients through the productive MSME program at LAZISMU Kudus as well as the obstacles in determining mustahik eligibility and solutions for facing obstacles in productive tithes at LAZISMU Kudus Regency. Second, to determine the mustahik mentoring process at LAZISMU Kudus Regency to become muzakki. The type of research conducted by the author is field research and this research approach uses a qualitative descriptive method. The data sources used are primary and secondary data sources. For data collection research techniques using observation, interviews and documentation. While the data analysis techniques using data reduction method, data presentation and conclusions. It can be concluded that, first, the process of determining the eligibility of mustahik as productive zakat recipients by LAZISMU provides a survey form. From the survey form, you can see the mustahik’s income and dependents, and if income cannot meet basic needs, then you can be included in the mustahik classification by LAZISMU Kudus. The constraints faced in the productive zakat business through the MSME program at LAZISMU Kudus are due to a lack of human resources. Meanwhile, alternative solutions to deal with these obstacles are increasing the performance of each HR or amil zakat, especially in its management function so that the distribution of zakat can be optimal, conducting outreach and outreach regarding productive zakat to mustahik to build a business from the zakat assets obtained so that the assistance that has been provided LAZISMU Kudus can be used as a business that can increase mustahik’s income.